Functional Portrait of Irf1 (Orf19.217), a Regulator of Morphogenesis and Iron Homeostasis in Candida albicans - Wijlick, Lasse van; Znaidi, Sadri; Hernández-Cervantes, Arturo; Basso, Virginia; Bachellier-Bassi, Sophie; d’Enfert, Christophe (Frontiers in Cellular and Infection Microbiology, 2022)
The alternate growth of Candida albicans between a unicellular yeast form and a multicellular hyphal form is crucial for its ability to cause disease. Interestingly, both morphological forms support distinct functions during proliferation in the human host. We previously identified ORF19.217 (C2_08890W_A), encoding a zinc-finger transcription factor of the C2H2 family, in a systematic screen of genes whose overexpression contributes to C. albicans’ morphological changes. Conditional overexpression of ORF19.217 with the strong tetracycline-inducible promoter (PTET) resulted in a hyperfilamentous phenotype. We examined growth of the orf19.217 knockout-mutant in different hypha-inducing conditions and found that the mutant still formed hyphae under standard hypha-inducing conditions. To further investigate the function of Orf19.217 in C. albicans, we combined genome-wide expression (RNA-Seq) and location (ChIP-Seq) analyses. We found that Orf19.217 is involved in regulatory processes comprising hyphal morphogenesis and iron acquisition. Comparative analysis with existing C. albicans hyphal transcriptomes indicates that Orf19.217-mediated filamentation is distinct from a true hyphal program. Further, the orf19.217 knockout-mutant did not show increased sensitivity to iron deprivation, but ORF19.217 overexpression was able to rescue the growth of a hap5-mutant, defective in a subunit of the CCAAT-complex, which is essential for iron acquisition. This suggested that Orf19.217 is involved in regulation of iron acquisition genes during iron deprivation and acts in a parallel pathway to the established CCAAT-complex. Interestingly, the orf19.217-mutant turned out to be defective in its ability to form filaments under iron-deficiency. Taken together our findings propose that the transcription factor Orf19.217 stimulates expression of the hyphal regulators EFG1 and BRG1 to promote filamentous growth under iron deprivation conditions, allowing the fungus to escape these iron-depleted conditions. The transcription factor therefore appears to be particularly important for adaptation of C. albicans to diverse environmental conditions in the human host. In regard to the newly identified functions, we have given the regulator the name Irf1, Iron-dependent Regulator of Filamentation.